Holistic model as theoretical support in the prevention of consumption, production and reproduction of pornography - Alexis Conde Mérida; Patricia Arés Mussio; Natividad Guerrero Borrego (Medisur)
The theoretical foundations of sexuality study allows us to delve deeper into the processes associated with sexuality education in adolescents and young people in current Cuban society, influenced by the effects of new information technologies. The objective of this research is to analyze the theoretical references for the design of a psychoeducational strategy aimed at preventing the consumption, production and reproduction of pornography in nursing students. A bibliographic review was carried out, from the Eusebio Rubio's Holon Model references, of the Psychological Sciences’ theoretical assumptions; with the educational teaching process contributions of the Psychology subject. The integration of the holistic model and psychological sciences was of great value for the approach of a psychoeducational strategy aimed at the prevention of consumption, production and reproduction of pornography by university students; scientifically based, applicable for the education and promotion of responsible sexuality.